(untitled) (International Journal of Emerging Research in Arts, Science and Technology, 2026)
For Indian consumers, a convenient, user-friendly, and transparent mobile payment system is the Unified Payment Interface (UPI). The uptake of UPI has fallen short of expectations, even with its advantages and the increase in internet and smartphone users. Investigating the elements promoting UPI uptake, user satisfaction, loyalty, and word-of-mouth is crucial to comprehending this. The Technology Acceptance Model (TAM) is used in this investigation to assess user satisfaction, loyalty, and word-of-mouth, shifting the focus from UPI operations to adoption factors. Data collection was aided via a five-point Likert scale questionnaire. Google Form was used to build the questionnaire and it was circulated by providing links to respondents on social media. 269 of the 300 surveys that were provided were considered valid for additional examination. SEM-PLS version 4.1 was utilized. The study argues that perceived usefulness, trust, and ease of use all favourably impact consumers’ desire to use UPI. Furthermore, there is a high correlation between behaviour intention and user satisfaction, which increases word-of-mouth and loyalty. All things considered, the study model aids in explaining how various UPI elements impact young customers satisfaction, loyalty, and word-of-mouth. Keywords: Technology Acceptance Model (TAM), Unified Payment Interface (UPI), Satisfaction, loyalty, word-of-mouth